The Effect of Experiential Marketing on Customer Loyalty: A Case Study of PT. Kansas Berkah Mandiri - Aisyah Amajida Jauza; Leni Cahyani (Golden Ratio of Mapping Idea and Literature Format, 2026)
Customer loyalty is a critical element for business sustainability, especially in the service industry, where market competition is intense. One marketing approach considered effective at fostering loyalty is experiential marketing, which focuses on delivering meaningful, engaging experiences to customers. This study aims to examine the influence of experiential marketing on customer loyalty at PT Kansas Berkah Mandiri in 2025. A quantitative approach was employed, using a structured questionnaire distributed to 120 company customers. The data were analyzed using multiple linear regression to identify the effects of five experiential marketing dimensions: sense, feel, think, act, and relate. The results revealed that all five dimensions significantly and positively affect customer loyalty. These findings suggest that the company's efforts to create impactful customer experiences have strengthened loyalty. The study offers strategic insights for managers to enhance experience-based marketing efforts to retain customers in an increasingly competitive market landscape.